Periodontal Disease and Breast Cancer: A Meta-Analysis of 1,73,162 Participants - Shao, Jun; Wu, Lan; Leng, Wei-Dong; Fang, Cheng; Zhu, You-Jia; Jin, Ying-Hui; Zeng, Xian-Tao (Frontiers in Oncology, 2018)
Objective: To investigate the correlation between periodontal disease and breast cancer. Materials and methods: PubMed and China National Knowledge Infrastructure databases were searched up to February 8, 2018 for observational studies examining the association between periodontal disease and breast cancer. Study selection was conducted according to predesigned eligibility criteria, and two authors independently extracted data from included studies. Meta-analysis was performed using the Comprehensive Meta-Analysis v2 software and risk estimates were calculated as relative risks (RRs) with corresponding 95% confidence intervals (CIs). Results: A total of 11 study were included. Meta-analysis indicated that periodontal disease significantly increased the risk of breast cancer by 1.22-fold (RR = 1.22, 95% CI = 1.06-1.40). Amongst participants with periodontal patients and a history of periodontal therapy , the risk of developing breast cancer was not significant (RR = 1.23; 95% CI = 0.95-1.60). The association results between periodontal diseases and breast cancer were found to be- robust, as evident in the leave-one-out sensitivity analysis. Conclusions: Periodontal disease may be a potential risk factor for the development of breast cancer among women, and thus effective periodontal therapy may present as a valuable preventive measure against breast cancer.